Rethinking Intrusiveness: Exploring the Sequential Organization in Interactions Between Infants and Mothers - Fantasia, Valentina; Galbusera, Laura; Reck, Corinna; Fasulo, Alessandra (Frontiers in Psychology, 2019)
To date, studies investigating maternal postpartum depression (PPD) have mainly focused on identifying failures in interactions of postpartum depressed mothers and their infants, often attributed to single dysfunctional maternal behaviours. Intrusiveness has been identified as a typical dysfunctional behaviour characterizing mothers suffering from PPD. However, this view does not consider the co-constructed and sequential nature of social interactions, in which single behaviours cannot be conceived as isolated or disconnected units. The aim of the work presented in this paper was to explore the interactional dynamics underlying maternal behaviours previously identified as intrusive by mainstream literature on postpartum depression. Through a conversation analytical approach, we analysed filmed interactions between mothers with and without postpartum depression and their 3-months-old infants. The analyses of 4 selected episodes illustrate similar dyadic activities, yet presenting different levels of mutuality and affective attunement. Results showed two normative features of social interactions that contributed to the different quality in the mutual adjustment of the partners: interactional rhythm and preliminaries. Interactional rhythm refers to the structuring of infants’ spontaneous activity into a turn sequence, whereas preliminaries consist of verbal or nonverbal moves that anticipating following action. As evident from our analytical observations, what seems to be hindering of the mutual coordination (previously labeled as “intrusive”) is not based on specific individual behaviours but on the absence or violation of such interactional norms. Adopting an interactive and dynamical framework, we shifted the focus from maternal behaviours considered as dysfunctional to observing the unfolding of interactional aspects contributing to better or poorer sequential structuring. We argue that these aspects shape the possibilities for the infant’s participation. Finally, we discuss the theoretical and methodological implications of adopting a conversation analytical approach for a better understanding of the relational dynamics related to clinical and non-clinical interactions.